Exploring the Nexus between CO2 Emissions, Trade, and Sustainable Economic Growth: A Novel NARDL Approach - Mohsin, Muhammad; Shamsudin, Mad Nasir; Alshammary, Khalid Mahsan; Sarfraz, Muddassar (International Journal of Energy Economics and Policy, 2024)
This study investigates the nexus between CO2 emission, trade, Gross domestic product (GDP), and tourism in Pakistan during 1990-2019. We examined the asymmetric relationship between CO2 emission, international trade, Gross domestic product (GDP), and international tourism number of arrivals in Pakistan. Data Stationarity has been tested using the Augmented Dicky Fuller (ADF), Kwiatkowski-Phillips-Schmidt-Shin (KPSS), and Phillips-Perron (PP) tests for unit roots. We used the NARDL technique. Then a Granger Causality helped estimate the relationship between these environmental variables. If there is an asymmetric association between these variables, we estimate the non-linear auto-regressive distributed lag, which is the most applicable econometric estimate. The ARDL technique can potentially explore the dynamic nexus between CO2 emission, tourism, GDP, and trade. Our findings suggest a dynamic relationship between tourism, trade, CO2 emission, and GDP from Pakistan's perspective. The outcomes reveal that negative and positive shocks to trade, GDP, and tourism affect CO2 emissions in the short and long term. The Granger Causality findings also determined that causality is directed from Tourism toward CO2 emission, while unidirectional causality was found between CO2 emission and tourism. In this study, the graphs of the CUSUM and CUSUMQ determined the functional stability of the established relationship. This indicates that this model is a suitable and valuable strategy tool. Therefore, an increase or decrease in the macroeconomic series will cause variation in carbon emissions in Pakistan in the long -term. The finding benefits macro-level policymakers and will provide important insight for the relevant stakeholders.